Low-temperature thermosetting resin composition, anisotropic conductive film and connection structure

The low-temperature thermosetting resin composition, featuring alicyclic epoxy resin, crown ether, and thermal cationic polymerization initiator, addresses storage stability and curing challenges in anisotropic conductive films, ensuring reliable and stable connections by controlling curing conditions.

JP7653193B2Active Publication Date: 2025-03-28CHANGZHOU DECHUANG HIGH TECH MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024035450
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-11-30
Filing Date
2024-03-08
Publication Date
2025-03-28
Estimated Expiration
2044-03-08

AI Technical Summary

Technical Problem

Existing anisotropic conductive films face challenges with storage stability and low-temperature fast curing due to premature polymerization at temperatures around 40-60°C, leading to unreliable connections and warping of substrates during COG mounting.

Method used

A low-temperature thermosetting resin composition is developed, incorporating an alicyclic epoxy resin, a crown ether compound, and a thermal cationic polymerization initiator. The crown ether captures the initiator cation during storage, suppressing reaction progression, allowing for low-temperature and short-time curing while enhancing storage stability.

Benefits of technology

The solution achieves improved storage stability and reliable connections by preventing premature curing during storage and ensuring effective curing at low temperatures, thus reducing substrate warping and enhancing connection reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653193000001
    Figure 0007653193000001
Patent Text Reader

Abstract

To provide a low-temperature thermosetting resin composition, an anisotropic conductive film, and a connection structure.SOLUTION: A thermosetting resin composition is a low-temperature thermosetting resin composition that includes: an alicyclic epoxy resin; a crown ether compound, the content of which accounts for 0.05 wt.% to 5.0 wt.% of the low-temperature thermosetting resin composition, preferably 0.1 wt.% to 3.0 wt.%; a thermal cationic polymerization initiator; a film-forming additive component; and conductive particles. The low-temperature thermosetting resin composition is applicable for making an anisotropic conductive film and a connection structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to the field of adhesive connections of electronic components, and in particular to a low-temperature thermosetting resin composition, an anisotropic conductive film, and a connection structure. [Background technology]

[0002] In fields such as semiconductors and flat panel displays, anisotropic conductive films have advantages such as directional conductivity, and are therefore widely used in fields such as fixing electronic components or connecting circuits, for example, chip mounting (COG) in which an IC chip is directly mounted on a glass substrate, and mounting of flexible wiring boards (FOG).

[0003] As products such as semiconductors and displays become smaller and thinner, the mounting locations of electronic components are closer to the panel display, and IC chips and glass substrates are also becoming very thin. Thermocompression bonding during connection can cause problems such as component burn-in, or misalignment of circuit wiring after mounting due to the difference in thermal expansion of the opposing circuit substrate. In particular, in COG mounting, the anisotropic conductive film shrinks during curing or the difference in thermal expansion between the IC chip and the glass substrate causes the substrate to warp, resulting in uneven display on the display. From the viewpoint of production cost, it is necessary to complete the curing of the adhesive layer material that produces the anisotropic conductive film at a relatively low temperature (e.g., 140 to 150°C) and within a relatively short time (e.g., within 5 seconds) in order to reduce costs and improve production efficiency.

[0004] In order to realize the storage stability and low-temperature fast curing of the adhesive layer material of the anisotropic conductive film, low-temperature curing cationic curing systems are the main direction of development. When using an alicyclic epoxy compound with higher cationic polymerization reactivity than the general-purpose glycidyl ether compound, and when used in combination with a highly reactive cationic polymerization initiator without the polymerization reaction inhibition by oxygen, a relatively low curing temperature (for example, about 100°C) can be achieved. However, for example, polymerization can start even at a temperature of about 40 to 60°C, and the adhesive also hardens during the storage process, resulting in a problem of low storage stability.

[0005] In view of the above, it is necessary to provide a pressure-sensitive adhesive material that combines storage stability and low-temperature curing performance, and to improve the connection reliability of the anisotropic conductive film produced. Summary of the Invention

[0006] In view of this, in order to overcome any of the above-mentioned and at least one other drawbacks present in the prior art, the present disclosure provides a low-temperature thermosetting resin composition that uses an alicyclic epoxy resin, a crown ether compound, and a thermal cationic polymerization initiator as a film-forming additive component, and that utilizes the crown ether to capture initiator cations and inhibit the progress of the reaction during storage, thereby realizing curing at a low temperature and in a short time, while improving storage stability, and capable of producing an anisotropic conductive film with good connection reliability.

[0007] The present disclosure also provides a connection structure that reduces warping of the substrate by anisotropically conductively connecting a first electronic component and a second electronic component using a cured anisotropic conductive film, thereby achieving a stable connection state with low stress.

[0008] In order to achieve the above object, according to one aspect of the present disclosure, there is provided a low-temperature thermosetting resin composition, (A) an alicyclic epoxy resin; (B) a crown ether compound having a content of 0.05% by weight to 5.0% by weight, preferably 0.1% by weight to 3.0% by weight, based on the low-temperature thermosetting resin composition; (C) a thermal cationic polymerization initiator; (D) a film-forming additive; and (E) conductive particles; Including, The low-temperature thermosetting resin composition provides a low-temperature thermosetting resin composition that is applied to heat curing to produce an anisotropic conductive film.

[0009] According to an embodiment of the present disclosure, the thermal cationic polymerization initiator contains at least one of a quaternary ammonium salt composed of a quaternary ammonium cation and a borate-based anion, and a sulfonium salt composed of an aromatic sulfonium cation and a borate-based anion.

[0010] According to an embodiment of the present disclosure, the quaternary ammonium salts include dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, methylphenyldibenzylammonium tetrakis(pentafluorophenyl)borate, phenyltribenzylammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetrakis(pentafluorophenyl)borate, and N,N-diethyl-N-benzylanilinium boron tetrafluoride; and the sulfonium salts include p-hydroxyphenyl-benzyl-methylsulfonium tetrakis(pentafluorophenyl)borate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4-hydroxyphenyl-methyl-1-naphthylmethylsulfonium tetrakis(pentafluorophenyl)borate, and 5-hydroxyphenyl-methyl-1-naphthylmethylsulfonium tetrakis(pentafluorophenyl)borate. )borate, 4-hydroxyphenyl-methyl-(2-methylbenzyl)sulfonium tetrakis(pentafluorophenyl)borate, methylphenyl[(2-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, methylphenyl[(3-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, methyl-4-hydroxyphenyl[(2-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, methyl-4-hydroxyphenyl[(3-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, 7-[bis(p-tolyl)sulfonyl]-2-isopropylthioxanthenyl tetrakis(pentafluorophenyl)borate 4-(p-tert-butylphenylcarbonyl)-4'-bis(p-tolyl)sulfonyl-diphenylsulfide-tetrakis(pentafluorophenyl)borate.

[0011] According to the embodiment of the present disclosure, the content of the thermal cationic polymerization initiator is 0.05% by weight to 30% by weight, preferably 2% by weight to 15% by weight, based on the alicyclic epoxy resin.

[0012] According to an embodiment of the present disclosure, the crown ether compounds are 12-crown 4-ether, 15-crown 5-ether, 18-crown 6-ether, 24-crown 8-ether, benzo-15-crown 5-ether, benzo-18-crown 6-ether, benzo-12-crown 4-ether, dibenzo-15-crown 5-ether, dibenzo-18-crown 6-ether, dibenzo-21-crown 7-ether, dibenzo-24-crown 8-ether, tribenzo-18-crown 6-ether, 4 ,13-Diazo-18-crown 6-ether, dicyclohexyl-18-crown 6-ether, 4'-carboxybenzo-15-crown 5-ether, 4'-carboxybenzo-18-crown 6-ether, 4'-aminobenzo-15-crown 5-ether, 4'-acetylbenzo-15-crown 5-ether, 4'-acetylbenzo-18-crown 6-ether, 4'-nitrobenzo-15-crown 5-ether, 4'-nitrobenzo-18-crown 6-ether, 4'-bromobenzo-18-crown crown 6-ether, 4'-bromobenzo-15-crown 5-ether, 1-aza-15-crown 5-ether, 1-aza-18-crown 6-ether, 1-aza-12-crown 4-ether, 4,10-diaza-15-crown 5-ether, 4,10-diaza-12-crown 4-ether, N-phenylaza-15-crown 5-ether, N,N'-dibenzyl-4,13-diaza-18-crown 6-ether, 2-(methylol)-15-crown 5-ether, 2-(methylol)-12-crown 4-ether, 4,10-diaza-15-crown 5-ether, 4,10-diaza-12-crown 4-ether, N-phenylaza-15-crown 5-ether, N,N'-dibenzyl-4,13-diaza-18-crown 6-ether, 2-(methylol)-12-crown 4-ether, 4,10-diaza-15-crown 5-ether, 4,10-diaza-12-crown 4 ... The aryl ether is any one selected from the group consisting of 1,4-dichloro-1,4-diphenyl-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1

[0013] According to an embodiment of the present disclosure, the cycloaliphatic epoxy resin may be 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexane-1,3-dioxane, 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexanecarboxylate, 3,4-epoxy-3-methylcyclohexylmethyl-3,4-epoxy-3-methylcyclohexanecarboxylate, 3,4-epoxy-5-methylcyclohexylmethyl-3,4-epoxy-5-methylcyclohexanecarboxylate, 3,4-epoxy and at least one selected from the group consisting of bis(3,4-epoxycyclohexylmethyl)adipate, bis(3,4-epoxycyclohexane), bis(6-methylcyclohexylmethyl)-3,4-epoxycyclohexanecarboxylate, 6-methyl-3,4-epoxycyclohexylmethyl-6-methyl-3,4-epoxycyclohexanecarboxylate, ethylene bis(3,4-epoxycyclohexanecarboxylate), dicyclopentadiene diepoxide, bis(3,4-epoxycyclohexylmethyl)adipate, and methylene bis(3,4-epoxycyclohexane).

[0014] According to the embodiment of the present disclosure, the content of the alicyclic epoxy resin is 10% by weight to 60% by weight, preferably 20% by weight to 50% by weight, based on the low-temperature thermosetting resin composition.

[0015] According to an embodiment of the present disclosure, the film-forming additive component includes an epoxy resin or a phenoxy resin that is solid at room temperature; The epoxy resin is preferably at least one selected from the group consisting of bisphenol-type epoxy resins, novolac-type epoxy resins, naphthalene-type epoxy resins, and biphenyl-type epoxy resins, The phenoxy resin is preferably at least one selected from the group consisting of fluorene-type phenoxy resins, bisphenol-type phenoxy resins, novolac-type phenoxy resins, naphthalene-type phenoxy resins, and biphenyl-type phenoxy resins.

[0016] According to the embodiment of the present disclosure, the content of the film-forming additive component is 10% by weight to 70% by weight, preferably 20% by weight to 50% by weight, based on the low-temperature thermosetting resin composition.

[0017] According to an embodiment of the present disclosure, the conductive particles are at least one selected from the group consisting of nickel, cobalt, silver, copper, gold, palladium, solder, and metal-plated resin particles;

[0018] According to an embodiment of the present disclosure, the content of the conductive particles is 50 to 100,000 particles / mm 2 Conductive film, 200 to 70,000 pieces / mm 2 It is a conductive film.

[0019] According to another aspect of the present disclosure, there is provided an anisotropic conductive film obtained by thermally curing the above-mentioned low-temperature thermosetting resin composition.

[0020] According to the embodiment of the present disclosure, the heat curing temperature is 140 to 150° C., and the curing time is within 5 seconds.

[0021] According to yet another aspect of the present disclosure, there is provided a connection structure in which a first electronic component and a second electronic component are anisotropically conductively connected by utilizing the above-mentioned anisotropic conductive film.

[0022] The low-temperature thermosetting resin composition provided by the present disclosure is obtained by adding an alicyclic epoxy resin, a crown ether compound, and a thermal cationic polymerization initiator to the film-forming additive component, and by using the crown ether to capture the cations of the initiator during the storage process and inhibit the progress of the reaction, the composition achieves curing at a low temperature and in a short time while improving storage stability. This solves the problem that polymerization occurs even at 40 to 60°C when an alicyclic epoxy resin is used in the conventional technology, resulting in reduced storage stability.

[0023] The connection structure provided by the present disclosure has a stable connection state with low stress after curing, reduces warping of the board, and can significantly improve connection reliability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In order to make the objectives, technical solutions and advantages of the present disclosure clearer and more explicit, the present disclosure will be further described in detail below in conjunction with specific examples, but the present disclosure is not limited to the following embodiments.

[0025] The terms used in this specification are not intended to limit the present disclosure, but are merely intended to describe specific examples. Terms such as "having," "including," and the like used in this specification refer to the presence of a feature, step, operation, and / or component, but do not exclude the addition of one or more other features, steps, operations, or components. All terms used in this specification (including technical and scientific terms) have the meanings that are commonly understood by those skilled in the art, unless otherwise defined. However, the terms used in this specification should be interpreted to have a meaning consistent with the context of this specification, and should not be interpreted ideally or excessively literal.

[0026] In the process of realizing the present disclosure, it was found that a cationic curing composition using an alicyclic epoxy resin, a crown ether compound, and a thermal cationic polymerization initiator as a film-forming additive component of a low-temperature thermosetting resin composition uses a crown ether to capture the cations of the initiator and inhibit the progress of the reaction, thereby realizing curing at a low temperature and in a short time while improving storage stability. The anisotropic conductive film makes it possible to obtain a connection structure with high connection reliability by minimizing warpage of the substrate with a relatively low stress.

[0027] According to one embodiment of the present disclosure, the low-temperature thermosetting resin composition of the present disclosure is mainly composed of an alicyclic epoxy resin, a crown ether compound, a thermal cationic polymerization initiator, a film-forming additive component, and conductive particles as essential components. More specifically, the low-temperature thermosetting resin composition is (A) an alicyclic epoxy resin; (B) a crown ether compound whose content is 0.05% by weight to 5.0% by weight, preferably 0.1% by weight to 3.0% by weight, for example, 0.05% by weight, 0.1% by weight, 0.2% by weight, 0.3% by weight, 1.0% by weight, 2.0% by weight, 3.0% by weight, 4.0% by weight, 5.0% by weight, etc., relative to the low-temperature thermosetting resin composition; (C) a thermal cationic polymerization initiator; (D) a film-forming additive; and (E) conductive particles; Including, The low-temperature thermosetting resin composition provides a low-temperature thermosetting resin composition that is applied to heat curing to produce an anisotropic conductive film.

[0028] According to the examples of the present disclosure, the low-temperature thermosetting resin composition provided by the present disclosure is obtained by adding an alicyclic epoxy resin, a crown ether compound, and a thermal cationic polymerization initiator to the film-forming additive component, and by using the crown ether to capture the cations of the initiator during the storage process and inhibit the progress of the reaction, the composition is cured at a low temperature and in a short time, and the storage stability is improved. This solves the problem that when an alicyclic epoxy resin is used in the related art, the composition is polymerized even at 40 to 60°C, resulting in low storage stability. The connection structure provided by the present disclosure has a stable connection state with low stress after curing, reduces warpage of the board, and can significantly increase connection reliability.

[0029] According to the embodiment of the present disclosure, the alicyclic epoxy resin used in the present disclosure has a structure in which an epoxy is directly arranged on an alicyclic skeleton. The alicyclic epoxy resin is liquid at room temperature. From the viewpoint of reactivity, it is preferable that the epoxy is bifunctional or more. For example, 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexane-1,3-dioxane, 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexanecarboxylate, 3,4-epoxy-3-methylcyclohexylmethyl-3,4-epoxy-3-methylcyclohexanecarboxylate, 3,4-epoxy-5-methylcyclohexylmethyl-3,4-epoxy-5-methylcyclohexanecarboxylate, 3,4-epoxy-6 ... The epoxycyclohexane carboxylate may be at least one of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, 6-methyl-3,4-epoxycyclohexylmethyl-6-methyl-3,4-epoxycyclohexane carboxylate, ethylene bis(3,4-epoxycyclohexane carboxylate), dicyclopentadiene diepoxide, bis(3,4-epoxycyclohexylmethyl)adipate, methylene bis(3,4-epoxycyclohexane), and the like.

[0030] According to the embodiment of the present disclosure, the content of the alicyclic epoxy resin is 10% by weight to 60% by weight, preferably 20% by weight to 50% by weight, based on the low-temperature thermosetting resin composition. However, the content ratio of the alicyclic epoxy resin to the low-temperature thermosetting resin composition may be 10% by weight, 20% by weight, 30% by weight, 40% by weight, 50% by weight, 60% by weight, etc. If the content ratio of the alicyclic epoxy resin to the low-temperature thermosetting resin composition is less than 10% by weight, a sufficient cured product cannot be obtained, resulting in unstable connection characteristics. If it exceeds 60% by weight, the film-forming additive component becomes insufficient, resulting in insufficient film-forming properties, or the amount of conductive particles blended becomes insufficient, resulting in connection failure.

[0031] According to an embodiment of the present disclosure, the thermal cationic polymerization initiator contains at least one of a quaternary ammonium salt composed of a quaternary ammonium cation and a borate-based anion, and a sulfonium salt composed of an aromatic sulfonium cation and a borate-based anion.

[0032] According to embodiments of the present disclosure, the borate-based anion is preferably BF4- or (BX4), where X represents phenyl substituted with at least two or more fluorines or trifluoromethyls.

[0033] According to embodiments of the present disclosure, the quaternary ammonium salts include dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, methylphenyldibenzylammonium tetrakis(pentafluorophenyl)borate, phenyltribenzylammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetrakis(pentafluorophenyl)borate, N,N-diethyl-N-benzylanilinium boron tetrafluoride, and the quaternary ammonium salt compound may be, for example, the product manufactured by King Industries under the trade name "CXC-1821."

[0034] According to an embodiment of the present disclosure, the sulfonium salt may be p-hydroxyphenyl-benzyl-methylsulfonium tetrakis(pentafluorophenyl)borate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4-hydroxyphenyl-methyl-1-naphthylmethylsulfonium tetrakis(pentafluorophenyl)borate, 4-hydroxyphenyl-methyl-(2-methylbenzyl)sulfonium tetrakis(pentafluorophenyl)borate, methylphenyl[(2-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, methylphenyl[(3-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, ]sulfonium-tetrakis(pentafluorophenyl)borate, methyl-4-hydroxyphenyl[(2-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, methyl-4-hydroxyphenyl[(3-thioxanthenyl)methyl]sulfonium-tetrakis(pentafluorophenyl)borate, 7-[bis(p-tolyl)sulfonyl]-2-isopropylthioxanthenyltetrakis(pentafluorophenyl)borate, 4-(p-tert-butylphenylcarbonyl)-4'-bis(p-tolyl)sulfonyl-diphenylsulfide-tetrakis(pentafluorophenyl)borate.

[0035] According to the embodiment of the present disclosure, the content of the thermal cationic polymerization initiator is 0.05% by weight to 30% by weight, preferably 2% by weight to 15% by weight, based on the alicyclic epoxy resin. However, the content ratio of the thermal cationic polymerization initiator to the alicyclic epoxy resin may be 0.05% by weight, 0.1% by weight, 0.2% by weight, 0.5% by weight, 1% by weight, 2% by weight, 5% by weight, 10% by weight, 15% by weight, 20% by weight, 30% by weight, etc. By setting the content of the thermal cationic polymerization initiator within this range, the obtained anisotropic conductive film has excellent low-temperature and short-time curing properties and storage stability.

[0036] According to the embodiment of the present disclosure, the alicyclic epoxy resin and the thermal cationic polymerization initiator have good reactivity, and therefore the resin has excellent low-temperature curing properties, high heat resistance, and good adhesion to substrates. Due to the characteristic of excellent reactivity, the amount of uncured material remaining in the cured product can be reduced, and the increase in shrinkage stress can be suppressed even in a high-temperature and high-humidity environment, so that the high-temperature and high-humidity resistance can be improved.

[0037] According to an embodiment of the present disclosure, the crown ether compounds are 12-crown 4-ether, 15-crown 5-ether, 18-crown 6-ether, 24-crown 8-ether, benzo-15-crown 5-ether, benzo-18-crown 6-ether, benzo-12-crown 4-ether, dibenzo-15-crown 5-ether, dibenzo-18-crown 6-ether, dibenzo-21-crown 7-ether, dibenzo-24-crown 8-ether, tribenzo-18-crown 6-ether, 4 ,13-Diazo-18-crown 6-ether, dicyclohexyl-18-crown 6-ether, 4'-carboxybenzo-15-crown 5-ether, 4'-carboxybenzo-18-crown 6-ether, 4'-aminobenzo-15-crown 5-ether, 4'-acetylbenzo-15-crown 5-ether, 4'-acetylbenzo-18-crown 6-ether, 4'-nitrobenzo-15-crown 5-ether, 4'-nitrobenzo-18-crown 6-ether, 4'-bromobenzo-18-crown crown 6-ether, 4'-bromobenzo-15-crown 5-ether, 1-aza-15-crown 5-ether, 1-aza-18-crown 6-ether, 1-aza-12-crown 4-ether, 4,10-diaza-15-crown 5-ether, 4,10-diaza-12-crown 4-ether, N-phenylaza-15-crown 5-ether, N,N'-dibenzyl-4,13-diaza-18-crown 6-ether, 2-(methylol)-15-crown 5-ether, 2-(methylol)-12-crown 4-ether, 4,10-diaza-15-crown 5-ether, 4,10-diaza-12-crown 4-ether, N-phenylaza-15-crown 5-ether, N,N'-dibenzyl-4,13-diaza-18-crown 6-ether, 2-(methylol)-12-crown 4-ether, 4,10-diaza-15-crown 5-ether, 4,10-diaza-12-crown 4 ... The aryl ether is any one selected from the group consisting of 1,4-dichloro-1,4-diphenyl-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-2,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1,4-tetrafluoroethylene-1However, it is preferably any one of 18-crown 6-ether, benzo-18-crown 6-ether, dibenzo-18-crown 6-ether, tribenzo-18-crown 6-ether, and dicyclohexyl-18-crown 6-ether. From the viewpoint of the ease of obtaining the cation and the ease of obtaining an industrial product, it is preferably any one of 18-crown 6-ether, benzo-18-crown 6-ether, dibenzo-18-crown 6-ether, tribenzo-18-crown 6-ether, and dicyclohexyl-18-crown 6-ether.

[0038] According to the embodiment of the present disclosure, the present disclosure suppresses the progress of the reaction by capturing the free ammonium cations and sulfonium cations in the molecular holes of the crown ether, thereby improving the storage stability. Since the alicyclic epoxy resin and the thermal cationic polymerization initiator have good reactivity, the low-temperature curing property is excellent, and by suppressing the reaction activity by adding the crown ether under this condition, the low-temperature curing effect is excellent, while the stability of the low-temperature thermosetting resin composition is improved and the possibility of easy curing during storage is reduced.

[0039] According to the embodiment of the present disclosure, the crown ether can improve the storage stability without affecting the existing curing characteristics with a relatively small amount of addition. The content of the crown ether compound is 0.05% by weight to 5.0% by weight, preferably 0.1% by weight to 3.0% by weight, based on the low-temperature thermosetting resin composition. If the content ratio of the crown ether compound to the low-temperature thermosetting resin composition is less than 0.05% by weight, the effect of improving the storage stability cannot be achieved. If it exceeds 3.0% by weight, the water absorption rate increases or the connection reliability of the low-temperature thermosetting resin composition deteriorates.

[0040] According to the embodiment of the present disclosure, the film-forming additive component is a component for forming a film from the low-temperature thermosetting resin composition, and an epoxy resin or a phenoxy resin that is solid at room temperature is used as an essential component.

[0041] According to an embodiment of the present disclosure, the film-forming additive component includes an epoxy resin or a phenoxy resin that is solid at room temperature, the epoxy resin is preferably at least one selected from the group consisting of a bisphenol-type epoxy resin, a novolac-type epoxy resin, a naphthalene-type epoxy resin, and a biphenyl-type epoxy resin, and the phenoxy resin is preferably at least one selected from the group consisting of a fluorene-type phenoxy resin, a bisphenol-type phenoxy resin, a novolac-type phenoxy resin, a naphthalene-type phenoxy resin, and a biphenyl-type phenoxy resin.

[0042] According to an embodiment of the present disclosure, in consideration of film forming performance and processing performance, the epoxy resin is preferably a bisphenol type epoxy resin. Here, the epoxy resin may be a product of KUKDO CEMICAL under the trade name "YD-020", etc. The phenoxy resin may be a product of NIPPON STEEL CHEMICAL under the trade name "YP-50", etc.

[0043] According to embodiments of the present disclosure, further film-forming auxiliary components such as unsaturated polyester resin, saturated polyester resin, butadiene resin, polyolefin resin, etc. may be used.

[0044] According to the embodiment of the present disclosure, the epoxy resin and the phenoxy resin, which are solid at room temperature, are excellent in film-forming property, processability, and connection reliability, and do not inhibit the cationic polymerization reaction, so that the curing reaction can be completed under the low temperature and short time conditions of the alicyclic epoxy resin, the thermal cationic polymerization initiator, and the crown ether compound. Furthermore, even after a reliability test in a high temperature and high humidity environment, peeling from the connection part of the connection structure can be suppressed.

[0045] According to the embodiment of the present disclosure, the content of the film-forming additive component is 10% by weight to 70% by weight, preferably 20% by weight to 50% by weight, based on the low-temperature thermosetting resin composition. For example, it may be 10% by weight, 20% by weight, 30% by weight, 40% by weight, 50% by weight, 60% by weight, 70% by weight, etc. The film-forming additive component within this range can exhibit sufficient film-forming ability.

[0046] According to an embodiment of the present disclosure, the conductive particles are at least one selected from the group consisting of nickel, cobalt, silver, copper, gold, palladium, solder, and metal-plated resin particles.

[0047] According to the embodiment of the present disclosure, the conductive particle content is 50 to 100,000 particles / mm 2 Conductive film, 200 to 70,000 pieces / mm 2 It is a conductive film. For example, 50 pieces / mm 2 , 80 pieces / mm 2 , 100 pieces / mm 2 , 1000 pieces / mm 2 , 10000 pieces / mm 2 , 100000 pieces / mm 2 The amount of the particles present can be measured by observing the particles with an optical microscope and counting the amount.

[0048] According to the embodiment of the present disclosure, the average particle size of the conductive particles can correspond to the deviation of the wiring height, and can suppress the increase of the conductive resistance to suppress the occurrence of a short circuit. The particle size of the conductive particles is measured by a general particle size distribution measuring device, and the average particle size may also be measured by a particle size distribution measuring device. The average particle size is preferably 2.5 μm or more and 30 μm or less, more preferably 3 μm or more and 20 μm or less. For example, it may be 2.5 μm, 3 μm, 4 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc.

[0049] According to the embodiments of the present disclosure, the amount of conductive particles present in the low-temperature thermosetting resin composition can suppress a decrease in the conductive particle capture efficiency and suppress the occurrence of short circuits, and the conductive particles may be a product under the trade name "Mircopearl" manufactured by Sekisui Chemical Co., Ltd. and a product under the trade name "BRIGHT" manufactured by Nippon Chemical Industry Co., Ltd., etc.

[0050] According to the embodiments of the present disclosure, the components of the low-temperature thermosetting resin composition may appropriately contain inorganic fillers, organic fillers, silane coupling agents, colorants, etc. depending on the type of circuit board to be connected, and may be used according to an appropriate purpose.

[0051] According to the embodiment of the present disclosure, the inorganic filler may be silica, titanium oxide, aluminum hydroxide, etc., and silica can reduce the moisture absorption rate and linear expansion coefficient of the cured product and improve the elastic modulus, thereby improving the connection reliability. Titanium oxide can color the circuit connecting material black or white, etc., making it easy to check whether the circuit connecting material is attached to the appropriate position on the circuit board. Aluminum hydroxide plays a role in neutralizing the acid remaining in the cured resin and exerts a corrosion prevention effect on the circuit electrodes.

[0052] According to the embodiment of the present disclosure, the organic filler may be a fine particle composed of a copolymer component such as acrylic resin, silicone resin, butadiene rubber, polyester, polyurethane, polyvinyl butyral, polyarylate, polymethyl methacrylate, polystyrene, NBR, SBR, etc., or may be a fine particle having a core-shell structure. They may be used alone or in combination. Circuit connecting materials containing such organic fillers are effective in improving adhesion, stress relaxation after curing, and impact resistance.

[0053] According to the embodiment of the present disclosure, a silane coupling agent may be used to improve adhesion to a glass substrate. The silane coupling agent is not particularly limited, and may be appropriately selected according to the purpose, and may be, for example, an epoxy-based silane coupling agent, an acrylic-based silane coupling agent, a thiol-based silane coupling agent, an amide-based silane coupling agent, etc.

[0054] According to another aspect of the present disclosure, there is provided an anisotropic conductive film obtained by thermally curing the above-mentioned low-temperature thermosetting resin composition.

[0055] According to the embodiments of the present disclosure, when the above-mentioned anisotropic conductive film is used for conductive connection of electronic components, the anisotropic conductive film can be quickly cured at low temperatures, has good stability during storage, and can avoid hardening when stored at 40 to 60°C.

[0056] According to the embodiments of the present disclosure, the heat curing temperature is preferably 140 to 150°C, and may be, for example, 140°C, 142°C, 145°C, 148°C, 150°C, etc., and the curing time is within 5 seconds, and may be, for example, 1 second, 2 seconds, 3 seconds, 4 seconds, 5 seconds, etc.

[0057] According to an embodiment of the present disclosure, the method for producing an anisotropic conductive film provided by the present disclosure includes first uniformly dispersing an inorganic filling agent in an organic solvent such as toluene, then dissolving a film-forming additive in the dispersion solution, mixing an alicyclic epoxy resin, a crown ether compound, a thermal cationic polymerization initiator and conductive particles to prepare a coating material, forming the coating material into a film by a well-known film-forming method, and thermally curing the film at a low temperature to prepare an anisotropic conductive film.

[0058] According to the embodiment of the present disclosure, the anisotropic conductive film of the present disclosure may be a single layer or may have a two-layer structure including a layer containing conductive particles and a layer not containing conductive particles. By forming a two-layer structure, it is possible to improve the particle capture efficiency during connection, reduce the amount of expensive conductive particles used, and reduce manufacturing costs.

[0059] According to the embodiment of the present disclosure, the anisotropic conductive film may be applied to a thickness that can sufficiently embed the electrodes of the circuit board, but this is also determined by the size and number of the electrodes. Usually, the thickness should be 3 to 10 μmm thicker than the height of the electrodes.

[0060] According to yet another aspect of the present disclosure, there is provided a connection structure in which a first electronic component and a second electronic component are anisotropically conductively connected by utilizing the above-mentioned anisotropic conductive film.

[0061] According to an embodiment of the present disclosure, the first electronic component may be, for example, an electrode portion of a first circuit board, and the second electronic component may be, for example, a connection portion of a second wired circuit board.

[0062] According to the embodiment of the present disclosure, the anisotropic conductive film is preferably applied when a first circuit board such as an IC chip, COF, FPC, etc. is anisotropically conductively connected to a second wiring circuit board such as a glass circuit board, a plastic circuit board, a rigid circuit board, a ceramic circuit board, a polyimide circuit board, etc. Also, a well-known method may be used as a method for connecting electronic components to the anisotropic conductive film.

[0063] The low-temperature thermosetting resin composition, anisotropic conductive film and connection structure proposed in this disclosure provide a method with excellent storage stability and cost-effectiveness for the research of anisotropic conductive films, and have profound significance for the development of adhesive materials in electronic products. EXAMPLES

[0064] In order to make the objectives, technical solutions and advantages of the present disclosure clearer and more obvious, the present disclosure will be described in more detail below in conjunction with specific examples. Unless otherwise specified, the test materials and reagents used in the following examples can all be purchased as commercial products. Any specific techniques or conditions not specified in the examples are conventional methods, and can be carried out according to the techniques or conditions described in the literature in this field, or according to the product specifications.

[0065] Comparative Example 1: Low temperature thermosetting resin composition (3,4,3',4'-dicycloxyl)bicyclohexane (trade name TTA-800, manufactured by TETRA) is component (A), quaternary ammonium salt compound (trade name CXC-1821, manufactured by King Industries) is component (C), and phenoxy resin (product name YP-50, manufactured by Nippon Steel Chemical & Materials) is component (D), and the mixing ratio of each component is as shown in Table 1. In addition, conductive particles (E) (trade name: Mircopearl, manufactured by Sekisui Chemical Co., Ltd., Ni-plated resin particles) with an average particle size of 3 μm were uniformly dispersed to obtain a low-temperature thermosetting resin composition, that is, an adhesive composition. Furthermore, the adhesive composition was applied to a peelable PET film with a thickness of 50 μm using a coating device, and the adhesive layer was obtained with a thickness of 18 μm after hot air drying at 50° C. for 5 minutes. The mixing ratio of each component is as shown in Table 1.

[0066] Comparative Example 2: Low temperature thermosetting resin composition Compared to Comparative Example 1, component (C) was changed to an aromatic sulfonium salt (product name TR-TAG-50108, manufactured by TRONLY), and a pressure-sensitive adhesive layer was obtained in the same manner as in Comparative Example 1. The mixing ratio of each component is as shown in Table 1.

[0067] Example 1: Low-temperature thermosetting resin composition An adhesive layer was obtained in the same manner as in Comparative Example 1, except that 18-crown-6-ether (product name 18Crown-6, manufactured by Energy Corp.) was added as component (B) as compared to Comparative Example 1. The mixing ratio of each component is as shown in Table 1.

[0068] Example 2: Low-temperature thermosetting resin composition An adhesive layer was obtained in the same manner as in Comparative Example 1, except that 18-crown-6-ether (product name 18Crown-6, manufactured by Energy Corp.) was added as component (B) as compared to Comparative Example 2. The mixing ratio of each component is as shown in Table 1.

[0069] Example 3: Low-temperature thermosetting resin composition In comparison with Example 1, the component (D) was changed to a solid epoxy resin (product name YD-020, manufactured by KUKDO CHEMICAL Co., Ltd.) and mixed. The mixing ratio of each component is as shown in Table 1.

[0070] Example 4: Low-temperature thermosetting resin composition An anisotropic conductive film was obtained in the same manner as in Example 1, except that component (B) was changed to benzo-15 crown-5 ether (product name Benzo-15 Crown-5, manufactured by Energy Co., Ltd.) as compared with Example 1. The mixing ratio of each component is as shown in Table 1.

[0071] The low-temperature thermosetting resin compositions of Examples 1 to 4 and Comparative Examples 1 and 2 were subjected to performance measurements, and the specific measurement methods are as follows. 1. Measurement using a differential scanning calorimeter (DSC) The pressure-sensitive adhesive layer obtained in each of the Examples and Comparative Examples was measured using a differential scanning calorimeter (DSC250, manufactured by TA). The sample weight was 5 mg, the measurement temperature range was 50 to 250°C, and the heating rate was 10°C / min, and the heat generation start temperature, heat generation end temperature, and heat generation amount were measured. The results are shown in Table 1. 2. Evaluation of storage stability The adhesive layer obtained in each Example and Comparative Example was left in a thermostat at 40°C for 48 hours. DSC measurement was performed on the adhesive layer after leaving it at 40°C, and the storage stability was judged according to the rate of decrease in heat generation. If the rate of decrease was less than 10%, it was judged as ○, and if it was 10% or more, it was judged as ×. The results are shown in Table 1. Heat generation reduction rate (%) = [(heat generation before leaving at 40℃ - heat generation after leaving at 40℃) / heat generation before leaving at 40℃]

[0072] Example 5: Fabrication of a connection structure An IC chip (dimensions: 1.6 mm x 15.1 mm, bump height: 12 μm) and a glass substrate (OA-10G manufactured by Nippon Electric Glass Co., Ltd., dimensions 40 mm x 20 mm, thickness 0.5 mm, spacing of surface ITO (indium-tin oxide) wiring (wiring width 22 μm, line spacing width 8 μm)) were used, and the adhesive layer obtained in each example and comparative example was sheared to a size of 2 x 20 mm, attached to the glass substrate, and heated and pressurized under connection conditions of temperatures of 140°C and 160°C, pressure of 60 MPa, and time of 5 seconds. The IC chip and glass substrate were connected by the cured anisotropic conductive film, and a connection structure was obtained.

[0073] The performance of the connection structure of Example 5 was measured, and the specific measurement method was as follows. 1. Connection resistance measurement The connection resistance of the connection structure was measured after connection, and the connection resistance after exposure to a high temperature and high humidity environment (85°C / 85% RH / 500 hours) was also measured. Measurements were performed using a resistance meter (model number: RM3545, manufactured by HIOKI), and the resistance value was measured when a current of 1 mA was flowing using the four-terminal method. If the connection resistance value after exposure to high temperature and high humidity was less than 10 Ω, it was judged as ○, and if it was 10 Ω or more, it was judged as ×. The results are shown in Table 1.

[0074] [Table 1]

[0075] *TTA-800: Alicyclic epoxy resin (structural name: (3,4,3',4'-dicycloxyl)bicyclohexane, manufactured by TETRA) *18 Crown-6: Crown ether compound (Structural name: 18 Crown-6-Ether, Energy) *Benzo-15Crown-5: Crown ether compound (Structural name: Benzo-15Crown-5-Ether, manufactured by Energy Corporation) *CXC-1821: Quaternary ammonium salt (structural name: dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate) *TR-TAG-50108: Aromatic sulfonium salt (structural name: p-hydroxyphenyl-benzyl-methylsulfonium tetrakis(pentafluorophenyl)borate, manufactured by TRONLY) *YP-50: Phenoxy resin (Structural name: Bisphenol A type phenoxy resin, manufactured by Nippon Steel Chemical & Materials Co., Ltd.) *YD-020: Epoxy resin (Structural name: Bisphenol A type epoxy resin, manufactured by KOKUDO)

[0076] As can be seen from Table 1 above, the low-temperature thermosetting resin compositions of Examples 1 to 4 contain crown ether, and after standing at 40°C for 48 hours, the reduction rate of the calorific value was less than 10%, revealing good storage stability. The compositions of Comparative Examples 1 and 2 do not use crown ether, and after standing at 40°C for 48 hours, the calorific value was significantly reduced, resulting in poor storage stability.

[0077] In Example 5, the connection structures obtained using the low-temperature thermosetting resin compositions of Examples 1 to 4 were connected at a low connection temperature of 140°C, and the connection resistance value after exposure to high temperature and high humidity was less than 10Ω, demonstrating that the connection state was stable under low stress. When the connection structures were produced at a connection temperature of 140°C using the low-temperature thermosetting resin compositions of Comparative Examples 1 and 2, the resistance value after 85°C / 85% RH / 500 hours was 10Ω or more, and the connection state was unstable, because no crown ether compound was used.

[0078] As described above, the low-temperature thermosetting resin composition of the present disclosure has excellent storage stability and can be cured at a relatively low temperature (e.g., 140 to 150°C) in a short time (e.g., within 5 seconds), so that the connection state of the cured anisotropic conductive film is stable even under low stress.

[0079] The above-mentioned specific embodiments further explain the objectives, technical solutions, and beneficial effects of the present disclosure. The above contents are merely specific embodiments of the present disclosure and are not intended to limit the present disclosure. Any modifications, equivalent replacements, etc. made within the spirit and principles of the present disclosure are understood to be within the scope of protection of the present disclosure.

Claims

1. A low-temperature thermosetting resin composition comprising: (A) an alicyclic epoxy resin; (B) a crown ether compound having a content of 0.05% by weight to 5.0% by weight based on the low-temperature thermosetting resin composition; (C) a thermal cationic polymerization initiator; (D) a film-forming additive component; and (E) conductive particles; Including, The thermal cationic polymerization initiator contains a quaternary ammonium salt composed of a quaternary ammonium cation and a borate-based anion, The low-temperature thermosetting resin composition is a low-temperature thermosetting resin composition that is applied to heat curing for producing an anisotropic conductive film. However, the low temperature means 140 to 150°C.

2. The quaternary ammonium salt is selected from dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, methylphenyldibenzylammonium tetrakis(pentafluorophenyl)borate, phenyltribenzylammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetrakis(pentafluorophenyl)borate, and N,N-diethyl-N-benzylanilinium boron tetrafluoride; The low temperature thermosetting resin composition according to claim 1.

3. 2. The low-temperature thermosetting resin composition according to claim 1, wherein the content of the thermal cationic polymerization initiator is 0.05% by weight to 30% by weight based on the alicyclic epoxy resin.

4. The crown ether compounds include 12-crown 4-ether, 15-crown 5-ether, 18-crown 6-ether, 24-crown 8-ether, benzo-15-crown 5-ether, benzo-18-crown 6-ether, benzo-12-crown 4-ether, dibenzo-15-crown 5-ether, dibenzo-18-crown 6-ether, dibenzo-21-crown 7-ether, dibenzo-24-crown 8-ether, tribenzo-18-crown 6-ether, 4,13-diazo- 18-crown 6-ether, dicyclohexyl-18-crown 6-ether, 4'-carboxybenzo-15-crown 5-ether, 4'-carboxybenzo-18-crown 6-ether, 4'-aminobenzo-15-crown 5-ether, 4'-acetylbenzo-15-crown 5-ether, 4'-acetylbenzo-18-crown 6-ether, 4'-nitrobenzo-15-crown 5-ether, 4'-nitrobenzo-18-crown 6-ether, 4'-bromobenzo-18-crown 6- ether, 4'-bromobenzo-15-crown-5-ether, 1-aza-15-crown-5-ether, 1-aza-18-crown-6-ether, 1-aza-12-crown-4-ether, 4,10-diaza-15-crown-5-ether, 4,10-diaza-12-crown-4-ether, N-phenylaza-15-crown-5-ether, N,N'-dibenzyl-4,13-diaza-18-crown-6-ether, 2-(methylol)-15-crown-5-ether, 2-(methylol)-12-crown 4-crown-10-ether, 2-(methylol)-18-crown-6-ether, icosafluoro-15-crown-5-ether, dicyclohexenyl-18-crown-6-ether, 4'-formylbenzo-15-crown-5-ether, 4,7,13,21,24-hexaoxa-1,10-diazabicyclo[8.8]hexacosane, bis(1,4-phenylene)-34-crown-10-ether, and 18-crown-5[4-(2,4-dinitrophenylazo)phenol]; The alicyclic epoxy resins include 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexane-1,3-dioxane, 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexanecarboxylate, 3,4-epoxy-3-methylcyclohexylmethyl-3,4-epoxy-3-methylcyclohexanecarboxylate, 3,4-epoxy-5-methylcyclohexylmethyl-3,4-epoxy-5-methylcyclohexanecarboxylate, 3,4-epoxy-6- At least one selected from the group consisting of methylcyclohexyl carboxylate, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, 6-methyl-3,4-epoxycyclohexylmethyl-6-methyl-3,4-epoxycyclohexane carboxylate, ethylene bis(3,4-epoxycyclohexane carboxylate), dicyclopentadiene diepoxide, bis(3,4-epoxycyclohexylmethyl)adipate, and methylene bis(3,4-epoxycyclohexane). The low temperature thermosetting resin composition according to claim 1.

5. 2. The low-temperature thermosetting resin composition according to claim 1, wherein the content of the alicyclic epoxy resin is 10% by weight to 60% by weight based on the low-temperature thermosetting resin composition.

6. 2. The low-temperature thermosetting resin composition according to claim 1, wherein the content of the film-forming additive component is 10% by weight to 70% by weight based on the low-temperature thermosetting resin composition.

7. the conductive particles are at least one selected from the group consisting of nickel, cobalt, silver, copper, gold, palladium, solder, and metal-plated resin particles; The conductive particle content is 50 to 100,000 pieces / mm 2 The low-temperature thermosetting resin composition according to claim 1, which is a conductive film.

8. 8. An anisotropic conductive film obtained by thermally curing the low-temperature thermosetting resin composition according to claim 1.

9. 9. The anisotropic conductive film according to claim 8, wherein the heat curing temperature is 140 to 150° C. and the curing time is 5 seconds or less.

10. A connection structure comprising a first electronic component and a second electronic component that are anisotropically conductively connected by using the anisotropic conductive film according to claim 8.

Citation Information

Patent Citations

  • conductive adhesive composition

    JP1996511570A

  • Photopolymerizable composition, photocurable hardenable pressure sensitive adhesive sheet, and bonding of member

    JP2000144071A

  • Adhesive composition, adhesive for use in circuit connection, method for connecting circuits using the same, and connected body

    JP2006199778A

  • Anisotropic conductive film, connection method, and joined body

    JP2014212016A

  • Anisotropically conductive film

    JP2016177954A